In-situ Detection Method for Microplastics in Water by Polarized Light Scattering - Liu, Tong; Yu, Shijun; Zhu, Xiaoshan; Liao, Ran; Zhuo, Zepeng; He, Yanping; Ma, Hui (Frontiers in Marine Science, 2021)
Microplastics (MP) in water bodies become the widespread contaminants and cause ecological and economic hazards. The demand for detection of MP in water bodies is bursting. This paper proposes a method based on polarized light scattering which measures the polarization parameters of the scattered light at 120° to detect MP in water. This method takes the advantages of in-situ measurement of the individual particles and the experimental setup in principle is used. By use of the measured polarization parameters equipped by machine learning, the standard polystyrene spheres, natural water sample, and lab-cultured microalgae are explicitly discriminated, and MP with different physical and chemical properties can be differentiated. We can also characterize the weathering of different MP and identify the specific type from multiple types of MP. This study explores the capability of the proposed method to detect the physical and chemical properties, weathering state and concentration of MP in water which promises the future application in water quality sensing and monitoring.